Identification of Insulin-Mimetic Plant Extracts: From an In Vitro High-Content Screen to Blood Glucose Reduction in Live Animals - Verena Stadlbauer; Cathrina Neuhauser; Tobias Aumiller; Alexander Stallinger; Marcus Iken; Julian Weghuber (Molecules, 2021)
Type 2 diabetes mellitus (T2DM) is linked to insulin resistance and a loss of insulin sensitivity, leading to millions of deaths worldwide each year. T2DM is caused by reduced uptake of glucose facilitated by glucose transporter 4 (GLUT4) in muscle and adipose tissue due to decreased intracellular translocation of GLUT4-containing vesicles to the plasma membrane. To treat T2DM, novel medications are required. Through a fluorescence microscopy-based high-content screen, we tested more than 600 plant extracts for their potential to induce GLUT4 translocation in the absence of insulin. The primary screen in CHO-K1 cells resulted in 30 positive hits, which were further investigated in HeLa and 3T3-L1 cells. In addition, full plasma membrane insertion was examined by immunostaining of the first extracellular loop of GLUT4. The application of appropriate inhibitors identified PI3 kinase as the most important signal transduction target relevant for GLUT4 translocation. Finally, from the most effective hits in vitro, four extracts effectively reduced blood glucose levels in chicken embryos (in ovo), indicating their applicability as antidiabetic pharmaceuticals or nutraceuticals.